2020
DOI: 10.1002/mgg3.1367
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent de novo WFS1 pathogenic variants in Chinese sporadic patients with nonsyndromic sensorineural hearing loss

Abstract: Background Hereditary hearing loss (HL) is heterogeneous in terms of their phenotypic features, modes of inheritance, and causative gene mutations. The contribution of genetic variants to sporadic HL remains largely expanding. Either recessive or de novo dominant variants could result in an apparently sporadic occurrence of HL. In an attempt to find such variants we recruited 128 Chinese patients with sporadic nonsyndromic sensorineural HL (NSHL) and performed targeted deafness multigene sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…WFS1 is predominantly expressed in the spiral ganglion neuron [ 37 , 38 ], and impaired WFS1 function is related to the “postsynaptic” ANSD. Patients with WFS1 variants have been reported to have favorable outcomes after cochlear implantation [ 39 , 40 ]. Our patient with the WFS1 c.2051C>T (p.A684V) variant also exhibited good auditory and speech performances with CI.…”
Section: Discussionmentioning
confidence: 99%
“…WFS1 is predominantly expressed in the spiral ganglion neuron [ 37 , 38 ], and impaired WFS1 function is related to the “postsynaptic” ANSD. Patients with WFS1 variants have been reported to have favorable outcomes after cochlear implantation [ 39 , 40 ]. Our patient with the WFS1 c.2051C>T (p.A684V) variant also exhibited good auditory and speech performances with CI.…”
Section: Discussionmentioning
confidence: 99%
“…p.Ala684Val, a known mutational hotspot allele, often arose from de novo variants. The mode of inheritance of p.Ala684Val appears to be consistent among ethnic backgrounds, including Caucasian, Japanese, Chinese, and Taiwanese patients [ 19 , 47 , 57 , 58 ]. Putatively, fetuses with developmentally induced de novo variants may be at risk for more severe auditory phenotypes, necessitating CI at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we found a heterozygous missense pathogenic variant c.2590G > A, (p. Glu864Lys) in the WFS1 gene, which has been described previously. [6][7][8] These studies described that patients carrying this pathogenic variant were manifested as deafness and diabetes mellitus, so some researchers named it autosomal dominant transmission of DM and HI. [6][7][8] Masafumi K et al identified three pathogenic variants (p. A684 V, p. K836N, and p. E864 K) known to cause Wolfram-like syndrome from 8 variants.…”
Section: Discussionmentioning
confidence: 99%